Differential microbiological groups affecting the clotting properties of sheep milk - Jiménez L.; Garzón A.; Oliete B.; Romero J.; Jiménez-Rabadán P.; Ramón M.; Pérez-Guzman M.D.; Arias R. (The value chains of Mediterranean sheep and goat products. Organisation of the industry, marketing strategies, feeding and production systems, 2016)
Milk quality criteria are established in many countries according to a variety of requirements, in order to answer the need of milk processors and consumers. Moreover, sheep’s milk, unlike cows’ or goats’ milk, is used almost exclusively for the production of cheese so its quality is based not only on its nutrient content but also on its renneting ability, a key factor in cheese yield. However the technological properties of many Spanish breeds have not been fully studied. On the other hand, the differential microflora of milk has varied effects on the coagulation process of milk. Information of factors affecting the technological characteristics of sheep’s milk is scarce and research on the evolution of lactodynamographic parameters in relationship with the microbiological aspects of milk has been limited. The aim of this work was to study the relationship between differential microbiological quality and technological parameters. The differential microbiological analysis of milk gives a clear idea about milk quality depending of the group. When the differential counts are classified attending to r parameter, it is observed that the samples with higher counts have lower renneting times. On the other hand, the value of A30 parameter is affected by the counts of SPC, THERMO, PSYCHRO, PSEUDO, COLIT, LACT and STREP, as well as, the pH value. In view of the results it shows that it is necessary to continue studying the influence of the microbial load of sheep’s milk cheese, as the main product obtained from processing.
Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2015/06/16-18, Montpellier (France)